LEXICO-SEMANTIC FEATURES OF KINEM IN ENGLISH AND RUSSIAN LANGUAGES - Kendjayeva Zemfira Alimjanovna (Western European Studies, 2024)
Kinesis, or body language, is a fundamental aspect of human communication that conveys a wide range of semantic features. This article explores the notion of kinesis in linguistics and examines its various semantic functions. The study of kinesis in linguistics is important for understanding nonverbal communication, cross-cultural communication, forensic linguistics, and language development. Kinesis provides valuable insights into human communication, helping us to communicate more effectively and understand cultural differences. It also plays a significant role in language development, particularly in the acquisition of nonverbal communication skills.
Keywords: kinem; semantics; nonverbal; linguistics